2008
DOI: 10.1261/rna.1063708
|View full text |Cite
|
Sign up to set email alerts
|

A-to-I RNA editing alters less-conserved residues of highly conserved coding regions: Implications for dual functions in evolution

Abstract: The molecular mechanism and physiological function of recoding by A-to-I RNA editing is well known, but its evolutionary significance remains a mystery. We analyzed the RNA editing of the Kv2 K + channel from different insects spanning more than 300 million years of evolution: Drosophila melanogaster, Culex pipiens (Diptera), Pulex irritans (Siphonaptera), Bombyx mori (Lepidoptera), Tribolium castaneum (Coleoptera), Apis mellifera (Hymenoptera), Pediculus humanus (Phthiraptera), and Myzus persicae (Homoptera).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 50 publications
2
38
0
Order By: Relevance
“…Comparative analysis indicated that A-to-I editing usually occurred in highly conserved coding regions, but usually recoded less-conserved coding positions of these regions (46,52). Our analyses indicate that edited sites accumulate mutations much more rapidly than unedited sites, and thus evolution of sites undergoing mRNA editing is accelerated to enhance protein diversity (46,52).…”
Section: Rna Editing and Genetic Variationmentioning
confidence: 78%
See 4 more Smart Citations
“…Comparative analysis indicated that A-to-I editing usually occurred in highly conserved coding regions, but usually recoded less-conserved coding positions of these regions (46,52). Our analyses indicate that edited sites accumulate mutations much more rapidly than unedited sites, and thus evolution of sites undergoing mRNA editing is accelerated to enhance protein diversity (46,52).…”
Section: Rna Editing and Genetic Variationmentioning
confidence: 78%
“…Thus, physiologically beneficial ADAR targets are fixed by purifying selection. A few examples about convergent evolution of ADAR targets supported this scenario (18,42,(45)(46). In addition to recoding, a few beneficial ADAR targets in noncoding RNA are fixed (Fig.…”
Section: Random Selection and Fixation Model For The Emergence Of Novmentioning
confidence: 78%
See 3 more Smart Citations